2000
DOI: 10.1021/ja001476l
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dynamics of Hydride Transfer in Enzyme Catalysis

Abstract: One of the strongest experimental indications of hydrogen tunneling in biology has been the elevated Swain-Schaad exponent for the secondary kinetic isotope effect in the hydride-transfer step catalyzed by liver alcohol dehydrogenase. This process has been simulated using canonical variational transition-state theory for overbarrier dynamics and optimized multidimensional paths for tunneling. Semiclassical quantum effects on the dynamics are included on a 21-atom substrate-enzyme-coenzyme primary zone embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
257
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(289 citation statements)
references
References 46 publications
29
257
3
Order By: Relevance
“…The model also indicates an asynchronized hybridization for the donor and acceptor carbons, which was first identified for dihydrofolate reductase (DHFR) by QM/MM calculations (33). Finally, in accordance with the ensemble-averaged variational transition state theory (VTST) results from Truhlar, Gao, and co-workers (24,25), the model supports the recently articulated hypothesis that the inflated mSSEs reported for many ADHs since 1989 result from deflated 2°D/T KIEs because of the shorter donor-acceptor distance (DAD) required for D transfer (1,34). The present model mirrors some of the previous empirical calculations on ADH and other systems (16,17,22,23,35) but provides a more comprehensive molecular and electronic interpretation.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The model also indicates an asynchronized hybridization for the donor and acceptor carbons, which was first identified for dihydrofolate reductase (DHFR) by QM/MM calculations (33). Finally, in accordance with the ensemble-averaged variational transition state theory (VTST) results from Truhlar, Gao, and co-workers (24,25), the model supports the recently articulated hypothesis that the inflated mSSEs reported for many ADHs since 1989 result from deflated 2°D/T KIEs because of the shorter donor-acceptor distance (DAD) required for D transfer (1,34). The present model mirrors some of the previous empirical calculations on ADH and other systems (16,17,22,23,35) but provides a more comprehensive molecular and electronic interpretation.…”
supporting
confidence: 77%
“…Some empirical models (22,23) as well as quantum mechanical/molecular mechanical simulation (QM/MM) studies (24)(25)(26)(27) have achieved moderate success in replicating the observed 2°m…”
mentioning
confidence: 99%
“…One method that has been successfully introduced to computational enzymology is the ensembleaveraged variational transition-state theory with QM/MM sampling (EA-VTST-QM/MM), which has been applied to a number of enzyme systems. 2,3,[9][10][11][12][13] Both primary and secondary KIEs can be computed using the EA-VTST-QM/ MM method, and the method includes contributions of multidimensional tunneling. In another work, a grid-based hybrid approach was used to model quantum effects in hydrogen transfer reactions by numerically solving the vibrational wavefunction of the transferring hydrogen nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Under some conditions, such as high temperature, extremes of pH or mechanical forces, protein will unfold into random coil that loses biochemical function (Selkoe 2003). Since folding and unfolding are essential to life, literatures on the study of these processes are very rich (Gao and Truhlar 2002;Gao et al 2006;Freddolino et al 2010;Yang et al 2010;Alhambra et al 2000;Duan et al 2010;Shank et al 2010). And it has been greatly advanced in recent years by the development of fast time-resolved techniques.…”
Section: Introductionmentioning
confidence: 99%